Emancipation without Utopia: Subjection, Modernity, and the Normative Claims of Feminist Critical Theory. (2015) - Allen, Amy
Abstract : Feminist theory needs both explanatory‐diagnostic and anticipatory‐utopian moments in order to be truly critical and truly feminist. However, the explanatory‐diagnostic task of analyzing the workings of gendered power relations in all of their depth and complexity seems to undercut the very possibility of emancipation on which the anticipatory‐utopian task relies. In this paper, I take this looming paradox as an invitation to rethink our understanding of emancipation and its relation to the anticipatory‐utopian dimensions of critique, asking what conception of emancipation is compatible with a complex explanatory‐diagnostic analysis of contemporary gender domination as it is intertwined and entangled with race, class, sexuality, and empire. I explore this question through an analysis of two specific debates in which the paradoxical relationship between power and emancipation emerges in particularly salient and seemingly intractable forms: debates over subjection and modernity. Drawing on the work of Michel Foucault, I argue that a negativistic conception of emancipation offers the best way for feminist critical theory to transform the paradox of power and emancipation into a productive tension that can fuel critique.